2000
DOI: 10.1159/000028398
|View full text |Cite
|
Sign up to set email alerts
|

The CYP2C19 Enzyme Polymorphism

Abstract: The genetic test is gradually replacing probe drugs as the primary tool for screening populations for the CYP2C19 polymorphism. A full appreciation for the clinical and toxicological relevance of this genetic variation is presently limited. Further research is needed in several areas. The development and use of 3-D models of the CYP2C19 enzyme to automate and increase the rate at which CYP2C19 substrates are identified could reap great benefits. Meanwhile, clinical research should begin to determine whether th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
106
0
3

Year Published

2001
2001
2012
2012

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 152 publications
(113 citation statements)
references
References 44 publications
4
106
0
3
Order By: Relevance
“…However, in contrast to the Asian population, the prevalence of PM of CYP2C19 in Caucasians is much lower, that is, about 2.8 versus 21.3%, respectively, in Caucasians and Japanese. 81 Schwab et al 82 could show significant differences considering the efficacy of lansoprazole-based quadruple therapy between Caucasian patients carrying wild-type alleles, one and two CYP2C19 defect alleles with cure rates of 80.2, 97.8 and 100% in the respective groups. The authors concluded that eradication rates of H. pylori highly depend on CYP2C19 genotype in white patients if the standard doses of lansoprazole are administered within this regimen and carriers of CYP2C19 wild-type allele might benefit from a higher PPIs dosage.…”
Section: Ulcer Disease and Proton Pump Inhibitorsmentioning
confidence: 99%
“…However, in contrast to the Asian population, the prevalence of PM of CYP2C19 in Caucasians is much lower, that is, about 2.8 versus 21.3%, respectively, in Caucasians and Japanese. 81 Schwab et al 82 could show significant differences considering the efficacy of lansoprazole-based quadruple therapy between Caucasian patients carrying wild-type alleles, one and two CYP2C19 defect alleles with cure rates of 80.2, 97.8 and 100% in the respective groups. The authors concluded that eradication rates of H. pylori highly depend on CYP2C19 genotype in white patients if the standard doses of lansoprazole are administered within this regimen and carriers of CYP2C19 wild-type allele might benefit from a higher PPIs dosage.…”
Section: Ulcer Disease and Proton Pump Inhibitorsmentioning
confidence: 99%
“…8 Recently it has been shown that CYP2C19 has a role in the activation of clopidogrel, an antiaggregant drug. SNP variants of this enzyme interfere with the clinical activity of this drug, to the point where the FDA were induced to request a modification in the prescribing information of the drug.…”
Section: Introductionmentioning
confidence: 99%
“…More than 75 drugs are metabolized by CYP2D6, including antidepressants, selective serotonin reuptake inhibitors and opioids [2]. CYP2C19 metabolizes more than 25 drugs including proton pump inbibitors and some antidepressants [3]. Populations in different environments and with different genetic backgrounds show interethnic differences in drug metabolism [4].…”
Section: Introductionmentioning
confidence: 99%